The Analysis of the Effect of Determinant Factors of Palm Oil Plantation Sector on Agricultural Sector Growth in North Sumatera - Hasibuan, Ali Sandy; Fitrawaty, Fitrawaty; Rahmadana, M. Fitri (Budapest International Research and Critics University, 2020)
This study aims to analyze the influence of the area of oil palm plantations, oil palm production, and the number of the agricultural sector workforce on the agricultural sector PDRB in North Sumatra province. The data used are secondary data sourced from BPS North Sumatra province, namely PDRB variable in the agricultural sector, area of oil palm, palm oil production and the number of agricultural sector workforce in North Sumatra province in time series from 2008 to.d. 2017 in five districts namely, Asahan, Langkat, Labuhanbatu Utara, Labuhanbatu Selatan and Labuhan Batu districts. Data analysis was performed using the OLS (Ordinary Least Square) method with a panel data regression estimation model using the help of Eviews 10. The results of this study simultaneously showed that changes in the independent variables of land area, production and the total workforce of the agricultural sector together influenced Agricultural Sector PDRB variable significantly. While partially concluded that the variable area of land and oil palm production had a positive and significant effect on the PDRB of the agricultural sector in North Sumatra province, while the variable labor force in the agricultural sector had a negative effect on the PDRB of the agricultural sector in North Sumatra province.